Osteoporosis, Global and Iranian Aspects - B Larijani; MR Mohajeri Tehrani; Z Hamidi; A Soltani; M Pajouhi (Tehran University of Medical Sciences, 2004)
Osteoporosis, characterized by low bone mass and microarchitectural deterioration of bone tissue leading to enlarged bone fragility and a consequent increase in fracture risk is a leading cause of morbidity and mortality in elderly people. The mortality rate in elderly persons with hip fracture approaches 20%. Half of them will be disabled in the remained life. Iranian Multicenter Osteoporosis Study (IMOS) developed by Endocrinology and Metabolism Research Center of Tehran University of Medical Sciences (EMRC-TUMS) and Ministry of Health and Medical Education in 2000. The aim of this study with more than 6000 participitants, was to determine normal range of BMD in Iranian population and assessing the current calcium and vitamin D status in Iran. The results were used for determining the normrmogram of BMD in Iranians and prevalence of Vit-D deficinecy among them. This document outlines all aspects of osteoporosis including risk factors, diagnosis, treatment and prevention of osteoporosis.